Acute psychiatric symptoms in a young woman with anti‐N‐methyl D‐aspartate receptor encephalitis: A case of successful early diagnosis and therapeutic intervention. Issue 2 (7th February 2022) - Tominaga, Marie; Morikawa, Kyoko; Yamamoto, Hiroto; Ogawa, Yutaro; Kamimura, Naomi; Tsuneki, Ikunosuke; Yahata, Tetsuro; Tamura, Masaki; Yanase, Toru; Sato, Aki; Shibuya, Hiroyuki; Kurabayashi, Takumi
Abstract: This clinical image presents a report on the diagnosis and treatment of anti‐NMDAR encephalitis, a rare disease. This report emphasizes the importance of a differential diagnosis for acute psychiatric symptoms. Accurate and timely diagnosis is critical for the selection and implementation of treatment and for optimal patient outcomes.